2016
DOI: 10.1158/1055-9965.epi-15-1247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Framing of Health Disparities in Local Print News: Implications for Multilevel Interventions to Address Cancer Inequalities

Abstract: Background Americans remain under-informed about cancer and other health disparities and the social determinants of health (SDH). The news media may be contributing to this knowledge deficit, whether by discussing these issues narrowly or ignoring them altogether. Because local media are particularly important in influencing public opinion and support for public policies, this study examines the prevalence and framing of disparities/SDH in local mainstream and ethnic print news. Methods We conducted a multi-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
1
20
1
Order By: Relevance
“…Other work has explored the implications of reporting on health disparities in news (9). While local news outlets rarely mention health disparities (88), the way that the news frames these issues is consequential. News stories emphasize behavioral explanations for health disparities at the expense of broader social or economic explanations (65), and stories that explicitly compare racial/ethnic groups ("social comparison framing") can lead to (a) underestimates of disease risk among the less at-risk group ( 9) and (b) lower intentions to engage in relevant screening tests among the disadvantaged group (90).…”
Section: Discussionmentioning
confidence: 99%
“…Other work has explored the implications of reporting on health disparities in news (9). While local news outlets rarely mention health disparities (88), the way that the news frames these issues is consequential. News stories emphasize behavioral explanations for health disparities at the expense of broader social or economic explanations (65), and stories that explicitly compare racial/ethnic groups ("social comparison framing") can lead to (a) underestimates of disease risk among the less at-risk group ( 9) and (b) lower intentions to engage in relevant screening tests among the disadvantaged group (90).…”
Section: Discussionmentioning
confidence: 99%
“…These results are somewhat surprising. Past research in a non-rural setting suggested that local news coverage of cancer disparities was relatively limited [47] Understanding the source of health disparity information among rural respondents is an important next step, especially in terms of ensuring accurate and up-to-date information is communicated to targeted populations in the future. Greater awareness may be a result of personal experiences, as respondents mostly emphasized the burden of cancer for their own communities and social networks.…”
Section: Discussionmentioning
confidence: 99%
“…Media influences which issues the public are exposed to and thereby sets the public agenda [ 18 ]. Agenda-setting research has furthermore shown that news coverage plays a role in shaping public opinion and the local policy agenda, and that this role is more prominent for local-level news [ 19 ].…”
Section: Introductionmentioning
confidence: 99%